(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2023)
In the context of the Southern Cone dictatorships, the letter worked as a narrative resource that allowed clandestine militants to communicate with relatives. The letter was thus able to go beyond the framework assigned to it within the social space, because it helped to circulate a narrative that filtered through the repressive policies, also allowing children of dictatorship victims to reconstruct their parents’ lives and thus their own identity. The article examines the possibilities of biographical, political and affective construction from twenty-seven letters written by Fernando Vergara to his daughter Barbara compiled in the book, Letters to Barbara (2019). From these letters the following questions are posed: What role does the location of specific places play in the reconstruction of the father’s clandestine life? How does the in-situ performance and the journey through countries and places operate, that the daughter made when constructing her identity? And finally, how can these letters be read in the present?